Synthesis and antiproliferative activity of ionic platinum(II) triphenylphosphino complexes. (24th November 2016) - Belli Dell' Amico, Daniela; Labella, Luca; Marchetti, Fabio; Samaritani, Simona; Hernández-Fuentes, Gustavo Alejandro; García-Argáez, Aída Nelly; Dalla Via, Lisa
Graphical abstract: Dehalogenation of cis- [PtCl2 (PPh3 )(NCMe)], followed by ligand substitution afforded ionic complexes [PtCl(PPh3 )(L∧L)][BF4 ] {L∧L = 2, 2′-bipyridyl (1 ) 1, 10-phenanthroline (2 )} and [PtCl(PPh3 )(L)2 ][BF4 ] {L = pyridine (3 ), dimethyl sulfoxide (4 )}. The complexes were characterized by X-ray diffraction and spectroscopic techniques. Antiproliferative activity against MSTO-211H, HeLa and HepG2 tumor cell lines was evaluated in vitro . Abstract: Ionic platinum(II) complexes [PtCl(PPh3 )(L∧L)][BF4 ] {L∧L = 2, 2′-bipyridyl (1 ) 1, 10-phenanthroline (2 )} and [PtCl(PPh3 )(L)2 ][BF4 ] {L = pyridine (3 ), dimethyl sulfoxide (4 )} were synthesized by dehalogenation of cis- [PtCl2 (PPh3 )(NCMe)], followed by reaction with the suitable ligand. Chelating nitrogen ligands L∧L afforded single products, which were structurally characterized. In the other cases mixtures of geometric (L = pyridine) and/or coordination (L = dimethyl sulfoxide) isomers were observed in solution. In these cases the structures of the less soluble isomers were obtained via single crystal X-ray diffraction. All the complexes were tested in vitro for their antiproliferative activity on three human tumor cell lines: MSTO-211H, HeLa and HepG2.